2016
DOI: 10.1038/srep31345
|View full text |Cite
|
Sign up to set email alerts
|

Role of vacancies, light elements and rare-earth metals doping in CeO2

Abstract: The magnetic properties and electronic structures of pure, doped and defective cerium oxide (CeO2) have been studied theoretically by means of ab initio calculations based on the density function theory (DFT) with the hybrid HF/DFT technique named PBE0. Carbon (C), nitrogen (N), phosphorus (P), sulphur (S), lanthanum (La) and praseodymium (Pr) doped in CeO2 and CeO2 containing oxygen vacancies (Ov) were considered. Our spin-polarized calculations show that C, N, Pr dopants and Ov defects magnetize the non-magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 20 publications
(21 reference statements)
2
23
0
Order By: Relevance
“…We note that the CeO 2 phase is fully relaxed (data not shown here) in the ip direction due to the large lattice mismatch with STO (>1%), and therefore, the ip strain was not considered when inferring the Ce doping ratio from the op lattice constant. Ladoped CeO 2 can be regarded as a dilute magnetic oxide but the magnetization is usually at least two orders of magnitude lower than in manganites, 59,60 and hence its contribution to the overall magnetic signal is insignificant.…”
Section: Resultsmentioning
confidence: 99%
“…We note that the CeO 2 phase is fully relaxed (data not shown here) in the ip direction due to the large lattice mismatch with STO (>1%), and therefore, the ip strain was not considered when inferring the Ce doping ratio from the op lattice constant. Ladoped CeO 2 can be regarded as a dilute magnetic oxide but the magnetization is usually at least two orders of magnitude lower than in manganites, 59,60 and hence its contribution to the overall magnetic signal is insignificant.…”
Section: Resultsmentioning
confidence: 99%
“…A number of experimental works supported by DFT calculations point to defects like oxygen vacancies as the origin of room temperature ferromagnetism . On the contrary, some publications challenge this supposition on the basis of their experimental results .…”
Section: Sample Notations Average Particle Sizes Treatment Temperatmentioning
confidence: 99%
“…The magnetic properties and electronic structures of pure and Pr doped CeO 2 have been studied theoretically by means of ab initio calculations based on the DFT . Their spin‐polarized calculations showed that Pr dopants and oxygen vacancies defects magnetize the non‐magnetic CeO 2 in different degree.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…, whereas Li et al observed strong ferromagnetism. First principles calculations based on the density functional theory (DFT) have been applied to explore structural, electronic and magnetic properties of RE‐doped TiO 2 and CeO 2 NPs …”
Section: Introductionmentioning
confidence: 99%